Prospective study to assess the obstetric and perinatal outcome in fibroid complicating pregnancy - Mhatre, Shalaka Dilip; Vazirani, Ayushi; Selvam, Vidhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Fibroids are the most common benign tumour of the uterus. Complications ranges from approximately 10-40% in fibroid complicating pregnancy. The objective of the study was to assess obstetric and perinatal outcomes in fibroid complicating pregnancy. Methods: A prospective study was carried out over a period of 01 June 2019-30 October 2020 on 42 women diagnosed with fibroid uterus in pregnancy. The study was conducted in the Obstetrics and Gynaecology department of Sree Balaji Medical College and Hospital, Chennai. Routine basic investigations were done. Ultrasonogram was done at booking visit and during subsequent visits to assess the increase in the size of the fibroid and degeneration and other obstetric complications such as malpresentation and placenta previa. Results: Major proportion was in the younger age group of 25-35 years. Fibroids were more frequent in multigravidae 34 (80.96%), and primigravidae were 8 (19.04%). The reported incidence of fibroid in pregnancy ranges from 0.01%-10.7%. 27 (64.28%) women were asymptomatic during pregnancy. Out of 42 women, 10 (23.80%) were known cases of fibroid became pregnant, remaining 32 (76.19%) were diagnosed as having fibroid during routine antenatal visits. 2 women (22.22%) had pain, 3 of them (7.14%) had preterm labor, 3 (7.14%) had spontaneous miscarriage, 6 (14.2) had threatened abortion, and 1(2.3%) had abruption placentae and 1(2.5%) had placenta previa. Out of 39, 27 (69.23%) women had vaginal delivery of which 2 (7.40%) women had assisted vaginal delivery. Lower segment cesarean section done in 12 women (30.76%). 32 babies delivered (82.05%) appropriate for gestational age infants, 3 (7.69%) had LBW, and 4 (10.25%) were IUGR. Conclusions: Fibroid complicating pregnancy are associated with complications during the antepartum, intrapartum, and postpartum period hence a regular follow up and evaluation is a must. Most pregnancies with fibroids are asymptomatic but may adversely affect the obstetric and perinatal outcome.